2011
DOI: 10.11606/issn.2317-0190.v18i1a103458
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da mielopatia associada ao HTLV/paraparesia espástica tropical (TSP/HAM) nas atividades de vida diária (AVD) em pacientes infectados pelo HTLV-1

Abstract: Objetivo: Descrever o desempenho nas atividades de vida diária (AVD) em pacientes infectados pelo HTLV-1 com TSP/HAM e medir o impacto da doença sobre a qualidade de vida dos pacientes. Método: Trata-se de um estudo descritivo, de corte transversal. Um total de setenta e três pacientes com TSP/HAM acompanhados no Centro de HTLV da Escola Baiana de Medicina e Saúde Pública, Salvador, Bahia, Brasil foram selecionados. O índice de independência funcional foi calculada usando o Health Assessment Questionnaire (HAQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…Compared to the study by Coutinho et al, 25 in our study the domains physical aspects, functional capacity, and pain of HTLV-1 infected patients had more favorable levels (Coutinho et al found scores of 24.2, 27.1 and 41.7 respectively). However, in the reported study, all patients had symptoms of HAM/TSP, compared to only 30.1% in our study.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Compared to the study by Coutinho et al, 25 in our study the domains physical aspects, functional capacity, and pain of HTLV-1 infected patients had more favorable levels (Coutinho et al found scores of 24.2, 27.1 and 41.7 respectively). However, in the reported study, all patients had symptoms of HAM/TSP, compared to only 30.1% in our study.…”
Section: Discussioncontrasting
confidence: 84%
“…Among HTLV-1 patients, there were more females (71.7%), in line with other studies (66.6–83%). [14] , [15] , [16] , [25] , [26] , [27] Evolution to HAM/TSP has been described to be associated with female sex. 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among symptomatic patients, activity limitations were reported possibly because patients with TPS/HAM have functional problems that limit the performance of daily life activities. 26 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, asymptomatic patients had higher quality of life than did symptomatic patients, corroborating results from another study that reported low quality of life in patients with TPS/HAM. 34 These results may be explained because patients with TPS/HAM have greater impairment of quality of life domains than do asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%